The Philippine Maharlika investment fund - Montesclaros, Jose Ma. Luis P. (2023)
The Philippines is establishing a sovereign wealth fund to spur public infrastructure investments in preparation for 2025 when it no longer qualifies for aid as an upper middle-income country. This move has several policy implications and practical impact on state management of financial resources and the capital market for a nation accustomed to another way of government provision for economic and infrastructural goals.